Multimodal Characterization of Crystal Structure and Formation in Rubrene Thin Films Reveals Erasure of Orientational Discontinuities. (19th January 2023) - Tan, Jenna A.; Dull, Jordan T.; Zeltmann, Steven E.; Tulyagankhodjaev, Jakhangirkhodja A.; Johnson, Holly M.; Liebman‐Peláez, Alex; Folie, Brendan D.; Dönges, Sven A.; Khatib, Omar; Raybin, Jonathan G.; Roberts, Trevor D.; Hamerlynck, Leo M.; et al.
Abstract: Multimodal multiscale characterization provide opportunities to study organic semiconducting thin films with multiple length scales, across multiple platforms, to elucidate crystallization mechanisms of the various microstructures that impact functionality. With polarized scanning transmission X‐ray and 4D‐scanning transmission electron microscopy, hybrid crystalline structures in rubrene thin films in which large crystalline domains surround a common nucleus and transition to a spherulite morphology at larger radii is observed. These high‐resolution techniques reveal how azimuthal orientational discontinuities at smaller radii are erased as spherulite morphology takes hold. In situ crystallization in the films with optical microscopy is also captured, discovering the importance of considering the initial temperature increase of a film during thermal annealing over the crystallization timescale. This kinetic information of the radial crystallization rate and of corresponding film heating kinetics is used to estimate the temperature at which the larger crystalline regions transition into a spherulite. By combining the results obtained from the different characterization modes, it is learned that thermal conditions can sensitively affect the crystallization of rubrene and other organic thin films. The observations suggest opportunities for more complex temperature‐dependent processing to maximize hybrid structures' functionality in organic thin films and demonstrate that multimodal studies deepen the understanding of structure‐function dynamics. Abstract : X‐ray and electron microscopies reveal a hybrid platelet‐to‐spherulite crystalline microstructure in rubrene thin films, owing to non‐isothermal annealing conditions. Optical microscopy of in situ film crystallization during annealing provides kinetic information to estimate the temperature of the hybrid structure transition. This multimodal approach provides generalizable insight into the impacts of thermal conditions for organic semiconductor thin film processing.